SCHOOL HEAD PLANNING OF IMPLEMENTATION OF LEARNING MANAGEMENT IN SDN 135564 KOTA TANJUNGBALAI - Yusuf Hadijaya; M. Rafiquddin Nasution; Mhd. Rizal Fadillah Marpaung (Jurnal Sabilarrasyad, 2020)
Learning is a process of interaction between students and learning resources in a managed environment in order to achieve certain goals that have been set. Learning is also a process of change in personality in the form of conversation, attitudes, habits, and intelligence. This change is permanent in behavior that occurs as a result of practice or experience. The learning atmosphere is certainly a lively and pleasant atmosphere that is expected. While the expected learning process is an interactive, active, and participatory process. In addition, the role of the principal is also demanded in the implementation of good learning management, that is, the principal should arrange learning objectives in an operational form, then formulate learning objectives in the form of learning products, then formulate learning objectives in the form of student behavior, then formulate standard of behavior to be achieved, then each activity in the school contains one goal, namely learning, and finally the principal should formulate learning objectives in conditions where the behavior occurs